If You Book It, Will They Come? Attendance at Postdischarge Follow‐Up Visits Scheduled by Inpatient Providers. Issue 8 (1st August 2017) - Banerjee, Rahul; Suarez, Alex; Kier, Melanie; Jr., Steve Honeywell; Feng, Weiwei; Mitra, Nandita; Grande, David T.; Myers, Jennifer S.
Abstract : BACKGROUND: Postdischarge follow‐up visits (PDFVs) are widely recommended to improve inpatient‐outpatient transitions of care. OBJECTIVE: To measure PDFV attendance rates. DESIGN: Observational cohort study. SETTING: Medical units at an academic quaternary‐care hospital and its affiliated outpatient clinics. PATIENTS: Adult patients hospitalized between April 2014 and March 2015 for whom at least 1 PDFV with our health system was scheduled. Exclusion criteria included nonprovider visits, visits cancelled before discharge, nonaccepted health insurance, and visits scheduled for deceased patients. MEASUREMENTS: The study outcome was the incidence of PDFVs resulting in no‐shows or same‐day cancellations (NS/SDCs). RESULTS: Of all hospitalizations, 6136 (52%) with 9258 PD‐FVs were analyzed. Twenty‐five percent of PDFVs were NS/SDCs, 23% were cancelled before the visit, and 52% were attended as scheduled. In multivariable regression models, NS/SDC risk factors included black race (odds ratio [OR] 1.94, 95% confidence interval [CI], 1.63‐2.32), longer lengths of stay (hospitalizations ≥15 days: OR 1.51, 95% CI, 1.22‐1.88), and discharge to facility (OR 2.10, 95% CI, 1.70‐2.60). Conversely, NS/SDC visits were less likely with advancing age (age ≥65 years: OR 0.39, 95% CI, 0.31‐0.49) and driving distance (highest quartile: OR 0.65, 95% CI, 0.52‐0.81). Primary care visits had higher NS/SDC rates (OR 2.62, 95% CI, 2.03‐3.38) than oncologic visits. The time interval between discharge and PDFV was not associated with NS/SDC rates. CONCLUSIONS: PDFVs were scheduled for more than half of hospitalizations, but 25% resulted in NS/SDCs. New strategies are needed to improve PDFV attendance.